Intergenerational Mobility in Income and Economic Status in Ethiopia - Getinet Astatike Haile (Institute for the Study of Labor (IZA), 2016)
Using data from two comprehensive national labour force surveys conducted in 2005 and 2013, this paper examines the extent of intergenerational mobility in Ethiopia using monetary and non-monetary measures. Quantile regression and OLS based results suggest there is moderate level of "stickiness" in income mobility across generations. Sons are found to be more mobile than daughters both in monetary and non-monetary terms, although the mobility gap appears to have narrowed recently. There is virtually no evidence on intergenerational mobility in the context of low income countries in general and Sub-Saharan Africa in particular. The paper thus provides valuable insights into issues of intergenerational mobility in a low income country setting. The mixed approach used addresses possible measurement error in income, as well as offering a broader scope in examining intergenerational mobility.
Keywords: J62; D31; 330; intergenerational mobility; income; education; occupation; Ethiopia